THEORETICAL ISSUES OF SUSTAINABLE DEVELOPMENT EDUCATION AND EDUCATION SYSTEM SECURITY - Oyuntsetseg Densmaa; Gerelchimeg Kaliinaa; Tuul Sembeejav (International Journal of Innovative Technologies in Social Science, 2022)
Education for sustainable development is the key to ecologically oriented economic development by gradually balancing environmental and social development in line with the global vision of sustainable development in the 21st century. The concept of sustainable development has been the main focus and the concept of the world countries. It is the main subject of improving people’s living standards without exceeding the carrying capacity of ecosystems is understood as sustainable development, and the key to this development is to develop and nurture people in all aspects. In other words, sustainable development is the ability to harmonize human activities with the development process and to use the environment and natural resources to meet current needs without compromising the needs of future generations. The world countries around the world are linking economic growth to social, environmental, and security issues. The United Nations (UN) and its specialized agencies, focusing on development and the environment, convened two worldwide UN conferences in 1972 and 1992, setting out the main directions for humanity in the new century. This is the "21st Century Development Agenda" approved in 1992 in Rio de Janeiro. Chapter 36 of the program, entitled “Supporting Education, Public Awareness and Training”, emphasizes the importance of enhancing the role of education in achieving the Sustainable Development Goals, supporting all aspects of it, and raising public awareness through formal and non-formal education. This is the basis for the education of sustainable development.